2008
DOI: 10.2214/ajr.07.3340
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Unsuspected Pancreatic Cysts on MDCT

Abstract: OBJECTIVE-Current generation MDCT technology facilitates identification of small, nonenhancing lesions in the pancreas. The objective of this study was to determine the prevalence of findings of unsuspected pancreatic cysts on 16-MDCT in a population of adult out-patients imaged for disease unrelated to the pancreas. MATERIALS AND METHODS-Contrast-enhancedMDCT scans of the abdomen were reviewed from 2,832 consecutive examinations to identify pancreatic cysts. Patients with a history of pancreatic lesions or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
466
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 805 publications
(491 citation statements)
references
References 13 publications
10
466
0
15
Order By: Relevance
“…Over the last decade, we have seen a steady rise in the incidence of pancreatic cysts, estimated to be present in ~2.4% of the population [1,2]. This is largely due to an increase in the use of cross-sectional imaging investigations undertaken for other symptoms, and an improvement in high-definition radiological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, we have seen a steady rise in the incidence of pancreatic cysts, estimated to be present in ~2.4% of the population [1,2]. This is largely due to an increase in the use of cross-sectional imaging investigations undertaken for other symptoms, and an improvement in high-definition radiological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that pancreatic cysts are identified in 1.2% to 2.6% of abdominal computed tomography scans. 1,2 The prevalence increases with age and up to 24% of patients at autopsy have pancreatic cysts. 3 Historically, pseudocysts were thought to represent the bulk of pancreatic cysts, but cystic neoplasms actually account for the majority of these lesions.…”
mentioning
confidence: 99%
“…Pancreatic cysts are now being discovered in large numbers of patients due to the increased use of high resolution CT and MRI diagnostic imaging, with as many as 14% of MRI scans and 3% of CT scans incidentally discovering the presence of pancreatic cysts 3436 . Because some pancreatic cysts are precancerous, and because pancreatic cancer is such a deadly condition, diagnosing the type of pancreatic cyst lesion accurately is a high stakes challenge.…”
Section: Discussionmentioning
confidence: 99%